Physicochemical and antioxidative properties of black, brown and red rice varieties of northern Thailand - Noppawat Pengkumsri (2018)
© 2015, Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA. All rights reserved. Rice, the seed of Oryza species, is the major cereal crop in most of the developing countries. Nearly 95% of global rice production is done in Asian countries, and about half of the world’s population consumes it. Some speciality rices are not commonly consumed. Colored rice is one of such variety. In these varieties, high amounts of anthocyanin pigment are deposited in the rice coat to form its black (also known as purple), brown and red colors. Minimum studies are there to explain the properties of these rice varieties of Thailand. Thus, the current study was aimed to assess the physicochemical and antioxidative properties of three rice varieties (Chiang Mai Black rice, Mali Red rice and Suphanburi-1 Brown rice) of different cultivars of northern Thailand. Rice bran extracts of these three cultivars were prepared with different solvents (polar and non-polar) for the evaluation of total phytochemical content and anti-oxidant free-radical-scavenging properties. Chiang Mai Black rice contained higher concentration of phenolic acid, flavonoids, and anthocyanins (Cyanidin 3-glucoside, peonidin 3-glucoside, cyanidin chloride). Chiang Mai Black rice is richer in free-radical-scavenging compounds and activities than the other tested varieties. Polar extractions of rice bran are high in anti-oxidative compounds and activities than non-polar extractions.